2022
DOI: 10.1371/journal.pone.0268462
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to intimate partner violence and the nutritional status of women and children in Nigeria

Abstract: Background Globally, intimate partner violence (IPV) epitomizes a greater proportion of the violence experienced by women, with more than a third of women (41.3%) in sub-Saharan Africa reporting IPV during their lifetime. This study examined the association between exposure to IPV and the nutritional status of women and their children in Nigeria. Methods The study analyzed secondary data obtained from the 2018 Nigeria Demographic and Health Survey. Data on women’s lifetime experience of psychological, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…This protective association could potentially stem from situations where aggressive behaviour towards the wife is followed by increased provision of food for the family due to feelings of guilt. Alternatively, it could be attributed to mothers overcompensating in terms of fulfilling the nutritional needs of their children, often referred to as a compensatory mechanism 40 41. Furthermore, it is likely that reverse causality is at play, wherein malnutrition, including child stunting, triggers aggressive behaviour in fathers owing to child neglect, ultimately leading to maternal exposure to IPV15 40; however, this reverse causality seems relatively unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protective association could potentially stem from situations where aggressive behaviour towards the wife is followed by increased provision of food for the family due to feelings of guilt. Alternatively, it could be attributed to mothers overcompensating in terms of fulfilling the nutritional needs of their children, often referred to as a compensatory mechanism 40 41. Furthermore, it is likely that reverse causality is at play, wherein malnutrition, including child stunting, triggers aggressive behaviour in fathers owing to child neglect, ultimately leading to maternal exposure to IPV15 40; however, this reverse causality seems relatively unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Various research from across the globe has examined the relationship between IPV and children’s nutrition status under 5 years of age 13 40 49 50. These studies have consistently identified a significant association between IPV and children’s nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 56% of women experienced at least one form of IPV in 2010 [22]. In the study setting, we believe patriarchy, social and cultural gender norms, power dynamics, and hierarchical constructions of masculinity and womanliness are the driving forces behind IPV [11]. Moreover, the COVID-19 pandemic has played a role in increasing IPV prevalence [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to different studies, growing up in a home with violence puts children on the trajectory of either becoming victims or perpetrators of domestic violence [10]. There is also evidence linking women's lifetime IPV exposure to their children's nutritional indicators, though the relationship has been inconsistent and varies depending on the context [11]. In India, maternal exposure to multiple incidences of physical family violence in previous years was linked to all measures of malnutrition, including stunting, wasting, and underweight in children aged 12-35 months [12].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of studies from Asia (6/11) (Ahmed et al, 2012;Fuada et al, 2020;Hossain et al, 2020;Mashal et al, 2008;Ngoc Hien & Ngoc Hoa, 2009;Nguyen et al, 2017) Nine studies in the qualitative synthesis presented data on moderate wasting in Asia (Ahmed et al, 2012;Akseer et al, 2018;Ali et al, 2019;Fuada et al, 2020;Hien & Kam, 2008;Mashal et al, 2008;Ngoc Hien & Ngoc Hoa, 2009;Nguyen et al, 2017Nguyen et al, , 2021 and 11 in SSA (Beiersmann et al, 2013;Boah et al, 2019;Friebert et al, 2017;Gbadamosi et al, 2017;Gewa & Yandell, 2012;Ickes et al, 2015;Issah et al, 2022;Mokwena & Kachabe, 2022;Olodu et al, 2019;Poda et al, 2017;Sobkoviak et al, 2012). For Asia, two-thirds of studies (6/9) reported an association between adolescent versus adult pregnancy and an increased risk of child wasting compared to approximately a quarter (3/11) of studies for SSA.…”
Section: Outcomes By Geographic Locationmentioning
confidence: 99%